T-cells contribute to hypertension but not to renal injury in mice with subtotal nephrectomy - Oosterhuis, Nynke R. (BMC Nephrol, 2017)
BACKGROUND: The pathological condition of chronic kidney disease may not be adequately recapitulated in immunocompromised mice due to the lack of T-cells, which are important for the development of hypertension and renal injury. We studied the role of the immune system in relation to salt-sensitive hypertension and renal injury in mice with subtotal nephrectomy (SNX). METHODS: Wild-type immunocompetent (WT) and Foxn1(nu/nu) athymic immunodeficient (AT) CD-1 mice underwent SNX to induce renal injury after which they received standard chow or a high salt diet (HSD). Four weeks after SNX blood pressure and kidney function parameters were measured. RESULTS: HSD increased albumin excretion independent of immune status. Systolic blood pressure increased only in WT mice on HSD, not in AT mice. Uremia and morphological damage after SNX were not affected by either HSD or immune status. CONCLUSIONS: For the development of hypertension after SNX in CD-1 mice mature T-cells and a high salt diet are required. SNX induced albuminuria was independent of the presence of T-cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12882-017-0555-0) contains supplementary material, which is available to authorized users.